Protecting the turf: The effect of territorial marking on others' creativity - Brown, Graham; Baer, M. (2015)
Territorial marking allows people to communicate that a territory has been claimed. Across 2 studies, we examine the impact of territorial marking of one's ideas on others' invited creativity when asked to provide feedback. Integrating research on territoriality and self-construal, we examine the effect of control-oriented marking on invited creativity (Study 1), and the extent to which an independent versus interdependent self-construal moderates this effect (Study 2). Results of Study 1 demonstrate that the use of control-oriented marking to communicate a territorial claim over one's ideas inhibits invited creativity, and this effect is mediated by intrinsic motivation. Also consistent with our hypotheses, the results of Study 2 show that self-construal moderates the effect of control-oriented marking on others' intrinsic motivation and creativity. Marking diminishes invited creativity among people with an independent self-construal but serves to enhance the creativity of those with an interdependent self-construal. Consistent with Study 1, intrinsic motivation mediates this moderated effect. Our results highlight the important but heretofore understudied role of territoriality in affecting others' creativity as well as the role of independent versus interdependent self-construal in shaping this effect.